Analisis Teknik Dasar Servis dalam Cabang Olahraga Bulu Tangkis - Ely Yuliawan; Ajeng Silvana Kartika; Miftahul Huda; M. Akbar Refkiansyah; Hafiz Ansori; Alim mukhti; indra Pahlawan (STKIP Subang, 2026)
Success in badminton stems from a comprehensive synergy of basic technical mastery, peak physical fitness, and stable mental readiness. This study focuses on analyzing the relationship between physical components and technical skills, particularly in service and smash execution, as key variables determining athlete performance. Utilizing a literature review method, this study synthesizes academic data encompassing the historical, technical, and physiological aspects of badminton. The analysis reveals that mastering service variations including long, short, drive, and flick services acts as a strategic tool to control the game's tempo from the outset. Physiologically, components such as VO2Max, agility, and leg muscle explosive power form the essential foundation for on-court mobility. Specifically, the research highlights that the combination of hand-eye coordination, arm power, and self-confidence contributes a significant 74.1% to the effectiveness of the smash. This study concludes that the integration of technical maturity, physical strength, and psychological readiness is an absolute necessity for achieving optimal athletic performance. Keywords: Badminton, Basic Technique, Service, Physical Condition, Smash.